Assessing the Effectiveness of Design Thinking to Foster Green Entrepreneurship Among Students: A Case Study in Mangrove Ecotourism - Kurniasih, Mima; Purwocaroko Noeringtyas, Billy (SKeTsa Bisnis (e-jurnal), 2025)
Introduction; Environmental issues in coastal areas, such as the reduction of mangrove forest area in Pesisir Timur Surabaya (PAMURBAYA), are driven by urban development and pose threats to human activities. This environmental challenge has sparked interest in entrepreneurship as a means to develop innovative and sustainable solutions. Increasing youth participation is seen as essential to balancing economic, social, and environmental benefits. Method; This study explores the effectiveness of Design Thinking in fostering a green entrepreneurial attitude among youth. The research focused specifically on business administration students participating in Design Thinking activities held at the mangrove ecotourism site in Gunung Anyar, Surabaya. A thematic analysis was conducted on the findings alongside a review of current literature to gain a deeper understanding. Results; The study found that the Design Thinking process successfully encouraged students to shift their mindset, enabling them to identify environmental problems as business opportunities. Students generated innovative, sustainability-oriented ideas, reflecting a change in attitude toward green entrepreneurship. Conclusion; This study contributes theoretically by demonstrating that Design Thinking can act as a catalyst for green entrepreneurship practices. Practically, it suggests integrating Design Thinking workshops into entrepreneurship courses to stimulate youth-led green business initiatives.